Representasi Stereotip Laki-Laki pada Media Perempuan: Analisis Semiotik pada Media Cosmopolitan.co.id - Fadhilah, Nadia Ayu; Razin, Muhammad Farras (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2024)
This article discusses the representation of male stereotypes in the media Cosmopolitan.co.id which is an online media owned by Cosmopolitan Indonesia with a target audience of women. This research aims to analyze the representation of male stereotypes in Cosmopolitan.co.id. The method used is Charles Sander Peirce's semiotic text analysis with the concept of a triadic relationship consisting of sign, object, and interpretant. The objects analyzed are four images and article texts in the Man Corner section at Cosmopolitan.co.id. The results showed that there are four forms of stereotypes of male characters in Man Corner articles, namely like to lie, sex-oriented, tend to be unfaithful to partners, and dominant in relationships. Cosmopolitan.co.id creates several forms of concerns, namely concerns about the partner and self which then directs self-evaluation. Cosmopolitan.co.id ultimately perpetuates stereotypes of men and creates women's anxiety, especially anxiety in relationships and anxiety towards partners.